2017
DOI: 10.1016/j.jadohealth.2017.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Beliefs Pertaining to Sexual and Reproductive Health Among Unmarried, Female Bhutanese Refugee Youth in Philadelphia

Abstract: Purpose We explored attitudes and beliefs pertaining to sexual and reproductive health (SRH) among unmarried, female, resettled Bhutanese refugees 16–20 years. Methods Fourteen interviews were analyzed using the constant comparison method, and major themes were identified. Results SRH was stigmatized for unmarried youth, making seeking information about SRH or accessing family planning difficult. There were many misconceptions about access to SRH. Conclusions Universal, culturally, and linguistically app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 7 publications
0
37
0
Order By: Relevance
“…Six studies were conducted in Australia [ 40 , 43 , 45 , 49 , 52 , 54 ], five in the USA [ 41 , 42 , 44 , 51 ], three in Canada [ 48 , 50 , 55 ] and Sweden [ 38 , 39 , 53 ], and one in the UK [ 46 ]. Studies included participants born in Bhutan [ 42 ], Cambodia [ 41 ], China [ 40 , 44 , 46 , 48 ], Iran [ 52 , 54 ], Malaysia [ 40 ], Japan [ 43 ], South Korea [ 53 ], and Thailand [ 38 , 39 , 53 ]. The term “Asian” was used to describe participants in five studies [ 45 , 49 , 50 , 51 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six studies were conducted in Australia [ 40 , 43 , 45 , 49 , 52 , 54 ], five in the USA [ 41 , 42 , 44 , 51 ], three in Canada [ 48 , 50 , 55 ] and Sweden [ 38 , 39 , 53 ], and one in the UK [ 46 ]. Studies included participants born in Bhutan [ 42 ], Cambodia [ 41 ], China [ 40 , 44 , 46 , 48 ], Iran [ 52 , 54 ], Malaysia [ 40 ], Japan [ 43 ], South Korea [ 53 ], and Thailand [ 38 , 39 , 53 ]. The term “Asian” was used to describe participants in five studies [ 45 , 49 , 50 , 51 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies were qualitative [ 38 , 40 , 41 , 42 , 43 , 46 , 48 , 49 , 50 , 52 , 53 , 54 ], using interviews ( n = 10) and focus groups ( n = 3). Remaining studies ( n = 4) used cross-sectional surveys [ 39 , 44 , 45 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Few qualitative studies on family planning in refugees resettled to the U.S. are available. A literature search revealed a single qualitative study evaluating family planning among refugees after resettlement to the U.S. Dhar and colleagues (2017) conducted 14 individual interviews with resettled Bhutanese adolescents. Their analysis indicated that family planning was stigmatized among non-married Bhutanese refugees.…”
Section: Introductionmentioning
confidence: 99%